Percutaneous Pulmonary Vein Stenting to Treat Severe Pulmonary Vein Stenosis After Surgical Reconstruction. Issue 4 (July 2020) - Dalal, Alex R; Markham, Ryan; Haeffele, Christiane; Sharma, Rahul; Watkins, A Claire
A 36-year-old female underwent left lower lobectomy with left atrial and left upper pulmonary vein (LUPV) reconstruction with a bovine pericardial patch for an intrathoracic pheochromocytoma. Postoperatively, she developed shortness of breath and transesophageal echocardiography demonstrated LUPV stenosis with increased velocities. Computed tomography angiogram of the chest revealed LUPV stenosis at the left atrium ostium with an area of 39 mm 2 . Under angiographic and echocardiographic guidance, a 10 × 19 mm Omnilink Elite uncovered stent was deployed in the LUPV ostia. While reported following left atrial ablation, pulmonary vein stenting can be successful in a pulmonary vein surgically reconstructed with bovine pericardium.